Physiological Gingival Melanin Hyperpigmentation Treatment with Injectable Vitamin C and Scalpel Technique: A Randomised Controlled Clinical Trial - Dhanashree S. Chaudhary; Simran R. Parwani; Shital Barkhade; Minal Gajbhiye; Rajkumar Parwani; Geetanjali Sikka; Kshipra Kawadkar; Nishita Jaju Soni; Niccolò Giuseppe Armogida; Himanshu Dadlani; Gianrico Spagnuolo (International Journal of Dentistry)
Harmony between facial complexion and gingival health goes hand in hand. Gingival depigmentation is an aesthetic correction of hyperactive melanocytes in gingival tissues that lead to hyperpigmentation. Current study compares depigmentation, pain scores, and itching with scalpel technique and nonsurgical intramucosal Vitamin C injection. 30 individuals in the age range of 18–40 years conscious of dark gums were randomly allocated to test and control group by lottery method. Thorough Phase I therapy was performed one week before the procedure. Area and intensity of depigmentation were evaluated preoperatively and postoperatively; pain score, itching, and repigmentation percentage were the postoperative parameters. After 24 hrs, test group showed significantly lesser VAS score for pain as compared to control group. There was no statistically significant difference in preoperative area of pigmentation between the test and control group (p=0.936). Postoperatively also, there was no statistically significant difference in area of pigmentation between the test and control group (p=0.932). For comparing area of pigmentation, an independent t-test was applied and Mann–Whitney test was used for differentiating the intensity of pigmentation, repigmentation, and VAS score between the groups. The study concluded that Vitamin C mesotherapy and scalpel technique showed comparable results in reduction of areas and intensity of gingival hyperpigmentation.